End Stage Renal Disease as a Potential Risk Factor for Retinal Vein Occlusion. Issue 47 (November 2015) - Chen, San-Ni; Yang, Te-Cheng; Lin, Jian-Teng; Lian, Ie-Bin
Abstract : Abstract: End stage renal disease (ESRD) has been reported to be an important risk factor for systemic vascular disease. Retinal vein occlusion (RVO) is closely related with cardiovascular diseases; however, its association with ESRD had not been reported. The aim of the study was to investigate whether ESRD is a risk factor for RVO, including central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO). This population-based study is based on the longitudinal data from Taiwan National Health Insurance Research Database. The study cohort comprised 5344 patients with diagnosis of ESRD on hemodialysis or peritoneal dialysis during the period from January 1996 to December 2011. For each ESRD patient, we selected 20 non-ESRD patients matched on age and sex. Each ESRD patient and his/her controls were followed from the initiation of renal dialysis until either the diagnosis of RVO or censorship. Kaplan–Meier method was used to compare the hazard of RVO between cohorts. Stratified Cox proportional hazard models were applied to estimate the hazard ratio (HR) adjusted by the comorbidities of RVO including diabetes mellitus (DM), hypertension, hypercholesteremia, and hypertriglyceridemia. After stratifying by DM status, the statistics were applied again to examine the associations among the DM cohort and non-DM cohort. The 16-year RVO cumulative incidence for ESRD cohort was 2-fold to the non-ESRD (1.01% vs 0.46%). After matching with age, sex, hypertension, and hypercholesteremia, the adjusted HR was 1.46 (95% confidence interval = 1.07–2.01, P value = 0.018). By further excluding patients with DM, the adjusted HR escalated to 2.43 (95% confidence interval = 1.54–3.83, P  < 0.001). In contrast, there was no significant risk of ESRD on RVO in the DM patients (HR = 1.03). We conclude that among the non-DM patients, ESRD cases had significantly higher RVO rate than the non-ESRD, which indicates that ESRD maybe a potential risk factor for the development of RVO in nondiabetic patients. Abstract : Supplemental Digital Content is available in the text